Bank Relationships and Private Firms' Financial Reporting Quality. Issue 2 (3rd April 2017) - Bigus, Jochen; Hillebrand, Christa
Abstract: Private firms with relatively high (proprietary) costs of disclosure may benefit from a close relationship with a bank. Relationship lending is based on intertemporal contracting that assumes that the bank is able to acquire private information about the firm and, moreover, to keep this information private. For both reasons, we expect and find that private firms with fewer bank relationships exhibit lower levels of financial reporting quality. Controlling for many other factors, firms with a single bank relationship disclose their financial reports about 14 days later. The size of such firms' financial reports is also smaller, containing approximately 8% fewer words than the median report. Firms with a single bank relationship also exhibit more earnings management, exceeding the median value of the three-year sum of absolute discretionary accruals by about 20%. The results are robust to different econometric specifications, including endogeneity concerns. They indicate that private firms choose to be opaque in the presence of fewer lending relationships.